Ignatian Spirituality as Inspiration for a Pedagogical Theory of Accompaniment - Marek, Zbigniew (Journal of religion and health, 2022)
The article presents Ignatian (Jesuit) spirituality as the source of a pedagogical concept that takes a subjective view of the human being regardless of their social position. Other subjects in the educational process (educator and personal God) are companions on the way to achieving good and developing one’s life potential. Another important aspect of Ignatian spirituality is the assumption that it can also perform a healing function, particularly transcendentally. This function concerns all the structures of human development and can be reflected in many ways of supporting human health. This perspective makes it possible to develop a model of Ignatian pedagogy in which the following elements are present: context, experience, reflection, action and evaluation. Recognising the educational values of these elements makes it possible to develop a pedagogical theory, called the pedagogy of accompaniment, which is reflected in a deep inner and outer sense of human existence. Thus, the purpose of this article is to describe the meaning of Ignatian spirituality for the pedagogy of accompaniment, with reference to its function of supporting the health of the human being, particularly the young.